Pengaruh Kepemimpinan Iklim Kerja dan Disiplin Guru terhadap Kinerja Guru di Yayasan Pendidikan Ibnu Halim Tanjung Mulia Medan - Bakhtiar Bakhtiar; Abdul Rasyid MS (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
The formulation of the problem in this study is how the influence of Leadership, Work Climate and Teacher Discipline on Teacher Performance at the Ibnu Halim Tanjung Mulia Education Foundation, Medan, either partially or simultaneously.The population and sample of this study were all teachers, totaling 40 people.The sampling technique uses total sampling.Data collection techniques used were direct interviews and questionnaires.The results of this study are that partially the leadership variable has a positive and significant effect on teacher performance with tcountttable, (2.345 1.67,), work climate has a positive and significant effect on teacher performance with tcountttable, (3.719 1.67) and the Discipline Variable has a positive and significant effect on Employee Performance with tcount ttable, (2.423 1.67).Simultaneously the variables Leadership, Work Climate and Discipline have a positive and significant effect on Teacher Performance with Fcount Ftable, (10.216 2.61).The R2 value (RSquare) is 0.524 which means that the variables of Leadership, Work Climate and Teacher Discipline have a positive and significant effect on Teacher Performance at the Ibnu Halim Tanjung Mulia Medan Education Foundation by 52.40%, and the remaining 47.60% again.